1994
DOI: 10.1017/s0007123400009790
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Linkages Between Democracy and Economic Growth

Abstract: Using cross-sectional and pooled data for up to 125 countries over the period from 1960 to 1985, this article evaluates the two-way linkages between democracy and economic growth. The effects of income on democracy are found to be robust and positive. The effects of several measures of democracy and personal freedoms on growth are assessed in a comparative growth framework in which growth of GDP per adult depends negatively on initial income levels, as implied by the convergence hypothesis, and positively on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
207
0
19

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(249 citation statements)
references
References 20 publications
11
207
0
19
Order By: Relevance
“…The coefficient of the interaction in column 1 stays robust to the inclusion of the democracy variable, which is still negative but gains in statistical power. It is interesting to see that positive democratic change itself has a negative effect on growth, which is in line with several previous studies (Gerring et al, 2005;Helliwell, 1994). In column 2, I control for the changes in the 'effective executive', which is determined by the form of governance: monarchy, presidential, parliamentarian, military or socialist.…”
Section: Robustness Testssupporting
confidence: 77%
“…The coefficient of the interaction in column 1 stays robust to the inclusion of the democracy variable, which is still negative but gains in statistical power. It is interesting to see that positive democratic change itself has a negative effect on growth, which is in line with several previous studies (Gerring et al, 2005;Helliwell, 1994). In column 2, I control for the changes in the 'effective executive', which is determined by the form of governance: monarchy, presidential, parliamentarian, military or socialist.…”
Section: Robustness Testssupporting
confidence: 77%
“…Barro (1996) and Helliwell (1994) found that these indices are positively related to economic growth only when some explanatory variables are omitted from the relationship such as: education and the investment rate.…”
Section: The Interpretation Of Resultsmentioning
confidence: 99%
“…Barro (1996) and Helliwell (1994) found that these indices are positively related to economic growth only when some explanatory variables are omitted from the relationship such as: education and investment rate. Isham et al (1997) analyzed the impact of the quality of governance on the performance of a hundred projects funded by the World Bank in some developing countries during the period 1974-1993.…”
Section: Civil Liberties Political and Economic Growthmentioning
confidence: 98%
See 1 more Smart Citation
“…5, No. 2;2013 influence on the environmental sustainability such as Helliwell (1994), Perrotti (1996) and Barret and Graddy (2000). According to them, countries with a high degree of civil and political liberty tend to take stern action against any pollution/decay to progress the quality of the environment.…”
Section: There Is a Negative Relationship Between Population Density mentioning
confidence: 99%